The study of indications, morbidity and mortality in patients delivered outside and referred to a tertiary care hospital - Shah, Tanvi D.; Ambadkar, Arun N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Emergency referral is critical to improving outcomes for time-sensitive conditions that underlie many unpredictable problems during pregnancy, delivery, and the postnatal period. This is especially true for poor, remote and rural populations where access to health services may be limited. So, this study evaluated the maternal and fetal outcomes in patients referred to a tertiary care hospital after delivery outside to note the commonest postpartum complications, morbidity and mortality indicators in terms of need of ICU, stay in hospital, need of dialysis, need of NICU. This paper described the application of a practical approach to the assessment of the burden of postpartum morbidity by means of postpartum referrals to tertiary centre. Methods: The observational present study was done in department of obstetrics and gynecology, BJ Government Medical College, Sassoon Hospital Pune covering a period of 18 months in postpartum period. Results: Study included 150 cases, out of these common reasons for referrals were pre-eclampsia/eclampsia (68%), post-partum hemorrhage (52.7%) and puerperal sepsis (26%) while anemia was observed in 70% cases. Conclusions: This study underscored the significant impact that delivering outside of a tertiary care setting can have on maternal-fetal outcomes. Timely referral to tertiary care centers plays a pivotal role in reducing complications and improving survival rates. Enhancing the quality of care in peripheral healthcare facilities and ensuring prompt transfer protocols could prevent many of the adverse outcomes.